The role of expenditure switching in the global imbalance adjustment - Wei Dong (Bank of Canada, 2010)
In theory, nominal exchange rate movements can lead to 'expenditure switching' when they generate changes in the relative prices of goods across countries. This paper explores whether the expenditure-switching role of exchange rates has changed in the current episode of significant global imbalances. We develop a multi-sector two-country model for the United States and the G6 countries, with the rest of the world captured by exogenous price and demand shocks, and estimate the model over two sub-samples, which cover the periods before and after the early 1990s. Our results indicate that both U.S. imports and exports have become much less responsive to exchange rate movements in recent years, mainly due to changes in firms' pricing behavior and the increased size of distribution margins. These findings suggest that the exchange rate would have to move by a much larger amount now than in the 1970s and 1980s to reduce the U.S. trade deficit by a given amount.
Keywords: F3; F4; 330; Exchange rates; international topics; Wechselkurspolitik; Außenhandelspreis; Preiswettbewerb; Konsumentenverhalten; Zahlungsbilanzungleichgewicht; Welt